Analysis of patch substructuring methods - Gander, Martin J.; Halpern, Laurence; Magoul?s, Frédéric; Roux, François-Xavier (Zielona Góra: Uniwersytet Zielonogórski)
Patch substructuring methods are non-overlapping domain decomposition methods like classical substructuring methods, but they use information from geometric patches reaching into neighboring subdomains, condensated on the interfaces, to enhance the performance of the method, while keeping it non-overlapping. These methods are very convenient to use in practice, but their convergence properties have not been studied yet.
Keywords: Schwarz domain decomposition methods; Schur complement methods; patch substructuring methods; optimized Schwarz methods